Cognitive Orientation to daily Occupational Performance (CO-OP) for mood, anxiety, and adjustment disorders: a pilot study - Wong, Su Ren; Chan, Mu Rong; Chong, Edlina; Dancza, Karina Michelle (Frontiers in Psychiatry, 2024)
Global mental health issues, particularly anxiety and depression, significantly impact people's everyday activities. While psychotherapies are commonly used, there is a growing interest in problem-solving approaches within mental health. These approaches focus on enabling individuals to develop personalized strategies to address emotional and psychological challenges and enhance their engagement in meaningful activities, known as occupational performance. This paper examines the feasibility of the Cognitive Orientation to daily Occupational Performance (CO-OP) in assisting adults with mood, anxiety, or adjustment disorders.The study employed a mixed methods single-subject design with replication, using an inductive/deductive approach for qualitative analysis. Ethical approval was obtained, and participants were recruited from a Singaporean hospital's occupational therapy service. CO-OP sessions were conducted either in-person or via telehealth. The intervention involved setting goals collaboratively, followed by weekly sessions over 10 weeks. Various data sources, including demographics, field notes, recordings of sessions, assessments and interviews were collected. Data analysis involved comparing pre-and post-intervention scores, thematic analysis of interviews, and triangulation of quantitative and qualitative data for validity. The study results are organized according to five feasibility domains: acceptability, demand, implementation, practicality, and limited efficacy.A total of 10 participants, mostly female, were recruited, with two dropping out during the baseline phase. All remaining participants completed the intervention and 1 month follow-up data collection. CO-OP was perceived as acceptable and beneficial in enhancing occupational performance, satisfaction and managing mood and anxiety symptoms. Participants expressed increased confidence and self-efficacy but desired continued therapist support for strategy application and reinforcement.Participants generally embraced CO-OP, favoring its personalized nature over therapistdirected approaches, with high retention rates observed. Building a strong therapeutic relationship was essential. Also using complementary approaches like supportive counseling proved beneficial. CO-OP emerges as a viable intervention alongside existing therapy approaches, offering a promising avenue for addressing the complex needs of individuals with mental health conditions.